KONSEP DIRI MAHASISWA LAKI-LAKI JURUSAN PENDIDIKAN GURU PENDIDIKAN ANAK USIA DINI (PAUD) DI UNIVERSITAS RIAU - Jafian Vernando Sinaga; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Universitas Riau is a state university located in Riau Province, the beginning of the establishment of Universitas Riau consisted of two faculties and one of them is the faculty of teacher training and education. Government attention to early childhood education marks its establishment of the department of eduacation teacher ECE in 2007 at the Universitas Riau. the department is considered to be more attached to women as a mother figure for children. the presence of men to be students at Department of Education Teachers ECE is a concern to knowing the background of choosing the department, the motivation of male students and their goals as male students in the majority of women. The theory used is George Herbert Mead, Self Concept (Symbolic Interactionalism), and the research method used is a qualitative approach method with in-depth interviews. The results showed that there was a background for male students who chose and took the Deprtment of Teacher Education ECE which was influenced by family and friends. After following the lecture process, the views of male students on the Department of Teacher Education ECE were influenced by lecturers and seniors who were the motivation for male students. The lowest need for appreciation is the recognition of status leading to the self-actualization of male students which results in achievement motivation to achieve self-activism that is related to expectations after graduating in Department of Teacher Education ECE. Keywords       :  Symbolic Interactionism, College Student, Department of Teacher             Education ECE